Genetic background influences cardiac phenotype in murine chronic kidney disease. Issue 7 (22nd December 2017) - Neuburg, Samantha; Dussold, Corey; Gerber, Claire; Wang, Xueyan; Francis, Connor; Qi, Lixin; David, Valentin; Wolf, Myles; Martin, Aline
ABSTRACT: Background: Levels of fibroblast growth factor 23 (FGF23) increase early in chronic kidney disease (CKD) and are independently associated with left ventricular hypertrophy (LVH), heart failure and death. Experimental models of CKD with elevated FGF23 and LVH are needed. We hypothesized that slow rates of CKD progression in the Col4a3 knockout (Col4a3 KO ) mouse model of CKD would promote development of LVH by prolonging exposure to elevated FGF23. Methods: We studied congenic Col4a3 KO and wild-type (WT) mice with either 75% 129X1/SvJ (129Sv) or 94% C57Bl6/J (B6) genomes. Results: B6-Col4a3 KO lived longer than 129Sv-Col4a3 KO mice (21.4 ± 0.6 versus 11.4 ± 0.4 weeks; P < 0.05). 10-week-old 129Sv-Col4a3 KO mice showed impaired renal function (blood urea nitrogen 191 ± 39 versus 34 ± 4 mg/dL), hyperphosphatemia (14.1 ± 1.4 versus 6.8 ± 0.3 mg/dL) and 33-fold higher serum FGF23 levels (P < 0.05 versus WT for each). Consistent with their slower CKD progression, 10 week-old B6-Col4a3 KO mice showed milder impairment of renal function than 129Sv-Col4a3 KO mice and modest FGF23 elevation without other alterations of mineral metabolism. At 20 weeks, further declines in renal function in B6-Col4a3 KO mice was accompanied by hyperphosphatemia and 8-fold higher FGF23 levels (P < 0.05 versus WT for each). Only the 20-week-old B6-Col4a3 KO mice developed LVH (LV mass 125 ± 3 versus 98 ± 6 mg; P < 0.05 versus WT) in association with significantly increased cardiac expression of FGF receptor 4 (FGFR4) messenger RNA and protein and markers of LVH (Atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), beta-myosin heavy chain (β-MHC); P < 0.05 versus WT for each). Conclusions: In conclusion, B6-Col4a3 KO mice manifest slower CKD progression and longer survival than 129Sv-Col4a3 KO mice and can serve as a novel model of cardiorenal disease.